VD_FINDINFO Décision / 2011 / 703 vom 30. Juli 2010 - VD Tribunal cantonal (2010)
DROIT TRANSITOIRE, DÉFAUTCONTUMACE | 271 CPP, 398 CPP, 403 CPP, 408 CPP, 398 al. 3 let. a CPP (CH), 407 al. 1 CPP (CH), 453 CPP (CH), 454 al. 1 CPP (CH)